A regularização fundiária em áreas de preservação permanente nas cidades sustentáveis - Moraes, Marina de Castro Oliveira (2015)
The work addresses the issue of land regularization of spontaneous settlements in areas of permanent preservation. It is noteworthy that the Federal Law No. 11,977, My House, My Life, constitutes, in an unprecedented way, an important device in favor of Land Regularization - albeit secondarily, because its main objective is to carry out a program specific government for construction of affordable housing. The instrument includes the interface with environmental issues, to consider the case of illegal occupation of APP. The paper also analyzes the reflections that the New Forest Code brought to the subject, from the moment you reported to your art. 3, XXVI, the provisions of art. 47, II of Law No. 11,977/ 2009 standard which establishes the program My House, My Life. It points out that the land tenure promotes citizen inclusion, as well as the preservation and sustainable use of the environment as a way of materialization of social and environmental role of urban property